DESIGN AND IMPLEMENTATION OF PLANE SEQUENCING ON AIR TRAFFIC CONTROL SIMULATOR - AKHMAD FITRIANTO (NIM: 23207115), ZAKI
ABSTRACT: Nowadays, air traffic is getting more and more crowd. Airport which has high air traffic should have mechanism that set how airplane take off and landing, so that the queue time is optimal. One of the technique is by doing sequencing to approaching plane. Sequencing is a process of establishing the order of arrival at a constraint point. Sequencing is one of the ways how ATC handles rush hour traffic. By doing sequencing, ATC operator is directing aircraft so that they form a convoy of one single ?le line as they progressively transition from the enroute phase of ?ight to the approach base and ?nally touch down on the runway. On this thesis is being designed and implemented, plane sequencing on Air Traffic Control (ATC). The graphic library used is OpenGL and GLUT as the utility toolkit. The operator of this simulator will face situation that there are several airplane move with different speed, different altitude and different direction, approaching airport. Operator's mission is to merge planes from different direction and then make them on sequenced condition. Operator use this simulator to train his/her ability on doing sequencing in order to reach optimal result. On this simulator, there are three ways to do sequencing. First is changing airplane's speed, second is changing airplane's altitude, and third is changing airplane's direction. This simulator uses 3 dimensional visualization. Operator can adjust the simulator visualization projection. Testing result shows that this simulator is support changing airplane's speed, airplane's altitude, and airplane's direction as a mechanism for operator on doing sequencing. But the operator sequencing optimal parameter is only using time needed by operator in doing sequencing. This operator sequencing optimal parameter need to be more explored.